A DEA MODEL FOR MEASURING EFFICIENCY ADAPTED TO THE HOTEL SECTOR - Escobar-Pérez, Bernabé; Lobo-Gallardo, Antonio; Otero-Terrón, José I. (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> The aim of this paper is propose an improved model based on the technique of Data Envelopment Analysis (DEA) to measure hotel efficiency. For that purpose, an extensive literature review has been carried out, focused mainly on empirical research. As a result, the proposed model incorporates some new operational variables widely accepted within the sector, like the REVPAR indicator, and allows to adapt the efficiency analysis to the current economic conditions and industry circumstances.